REAKSI PASAR MODAL TERHADAP PENCALONAN JOKOWI MENJADI PRESIDEN REPUBLIK INDONESIA - Yuniarthi, Ni Nengah Sureni; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This research was conducted at the company registered the Indonesia Stock Exchange. The number of samples taken are 483 company, with purposive sampling method. The analysis technique used is the one sample t-test (one-samples t test) and two different test paired samples (paired samples t-test). Based on the statistical test found that there is no capital market reaction at the time of nomination and before and after the nomination Jokowi became president of the Republic of Indonesia. It shows information about the presidential candidacy of Jokowi be able to anticipate as investors reflection of political events in advance and the information that goes into the capital markets will be analyzed by investors in decision-making.
Keywords: market reaction, abnormal return, event study